PENGARUH PERBEDAAN SUHU PENGERINGAN TERHADAP AKTIVITAS ANTIOKSIDAN DAUN JARAK PAGAR (Jatropha curcas L) - rahmayulis; Mega Yulia; Riflyani (LPPM Akademi Farmasi Imam Bonjol Bukittinggi, 2024)
Jatropha plant is a plant that contains secondary metabolites, including steroids, phenolics, flavonoids and saponins. Jatropha plants are also known to have antioxidant activity. This study aims to determine the best drying temperature for the antioxidant activity test of jatropha leaves. The antioxidant activity test was carried out by drying test jatripha leaves using ovens with different temperatures, namely temperatures of 40oC, 50oC and 60oC wich was then tested for antioxidant activity using the DPPH method (2-2 diphenyl-picrylhydrazil) using a UV-Vis Spectrophotometer. The results of antioxidant activity testing in Jatropha were obtained, at drying temperature 40oC IC50 value of 1,868.87 ppm, temperature 50oC IC50 value of 1,116.97 ppm and temperature 60oC IC50 value of 319,90 ppm. From the results of the study, it can be concluded that drying samples using an oven at 60oC has a better IC50 value than drying at 40oC and 50oC, which is 319,90 ppm and classified as weak antioxidants.